Monitoring Irish Coastal Heritage Destruction: A Case Study from Inishark, Co. Galway, Ireland - Sean Field; Ian Kuijt; Ryan Lash; Tommy Burke (Remote Sensing)
Coastal erosion poses an acute threat to cultural heritage resources, particularly in island contexts where erosional and degradational threats can be amplified by increased exposure and sea-level changes. We present a generalizable, best-practice approach that integrates multi-temporal, multi-resolution, and inconsistently ground-controlled data to demonstrate how suites of remotely sensed data can be integrated under real-world constraints. This approach is used to conduct a longitudinal analysis of cultural resources on the island of Inishark, Western Ireland. Results show evidence of significant and potentially accelerating shoreline erosion and structural loss within the past century, with rates of erosion ranging from 0.15 to 0.3 m/year along shorelines and 3–5 m2/year for structures. Outcomes demonstrate the utility and importance of an integrative data approach for cultural resource management.